PEMERIKSAAN KADAR HAEMOGLOBIN PADA IBU HAMIL DI LABORATORIUM PRODI KEBIDANAN AMBON POLTEKKES KEMENKES MALUKU - Wa Ode Rahmawati; Christina Lorince Ratulohain (Jurnal Kebidanan, 2022)
Policies related to pregnancy are the integrated Antenatal Care (ANC) program for every pregnant woman, namely the 14T examination in which there is an examination of hemoglobin levels. Checking hemoglobin (Hb) levels is carried out in the laboratory to determine red blood cell levels in pregnant women to ensure Hb levels are above 11 g/dL. If the Hb level is below 11 g/dL, then the pregnant woman has anemia which can disrupt the growth and development of the fetus and can cause a risk of bleeding in the mother during delivery. The aim of this study was to determine the hemoglobin level of pregnant women. The type of research used is observational research with a prospective descriptive nature with a cross-sectional research design. The subjects of this study were third trimester pregnant women who had an examination at the Ambon Midwifery Study Program Laboratory. The result showed that 60% of the 20 respondents (12 pregnant women) had normal Hb levels, while 8 pregnant women (40%) had abnormal Hb levels. There are more pregnant women with Hb levels ≥ 11.0 g/dL than pregnant women with Hb levels < 11.0 g/dL. It is recommended that pregnant women carry out routine pregnancy checks at the Public Health Center and take Fe tablets as recommended and consume nutritious food.